Escuelas de juristas y argumentación dialéctica - Fuentesca, Margarita (Tesserae iuris, 2023)
The passages in the Roman sources that expressly describe a discussion between the two schools of jurists in Rome, the Cassiani and the Proculiani, are analysed here. In all of them, the arguments concerning a specific legal institution are presented in the form of dialectical argumentation, i.e. a thesis is stated, which is opposed by an antithesis, with their respective arguments, in order to reach a synthetic conclusion between the two theories.